2020
DOI: 10.1021/acs.macromol.0c00550
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition of Disentangled and Entangled Polymer Melts: Single-Chain-Nanoparticles Approach

Abstract: We study the effect of entanglements on the glass transition of high molecular weight polymers, by the comparison of single-chain nanoparticles (SCNPs) and equilibrated melts of high-molecular weight polystyrene of identical molecular weight. SCNPs were prepared by electrospraying technique and characterized using scanning electron microscopy and atomic force microscopy techniques. Differential scanning calorimetry, Brillouin light spectroscopy, and rheological experiments around the glass transition were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Singh et al. [ 114 ] even suggested that local packing dominates the glass transition process and that topological constraints due to chain entanglements do not play a significant role. More evidence is needed to further examine the impact of entanglement on T g .…”
Section: Effect Of Entanglement On the Polymer Propertiesmentioning
confidence: 99%
“…Singh et al. [ 114 ] even suggested that local packing dominates the glass transition process and that topological constraints due to chain entanglements do not play a significant role. More evidence is needed to further examine the impact of entanglement on T g .…”
Section: Effect Of Entanglement On the Polymer Propertiesmentioning
confidence: 99%
“…The topological and/or architectural differences can have a large impact on the molecular behavior. Different chemical and physical properties, such as density [ 8 ], hydrodynamic size [ 8 , 9 , 10 , 11 , 12 ], viscosity [ 13 , 14 , 15 , 16 , 17 ], glass transition temperature [ 18 ], strength [ 19 ], and the dynamics [ 20 ], are affected by chain topology and/or architecture [ 21 , 22 ]. Scattering techniques present a great opportunity to study the intra-molecular cross-linking effects on SCNPs systems at a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the alternating distribution of amorphous regions between the lamellae. The melt stretching process leads to an increase in chain entanglement and an increase in the orientation of the carbon chain skeleton 50 . The highly oriented entangled molecular chains are confined between the lamellae, resulting in higher glass transition temperature.…”
Section: Resultsmentioning
confidence: 99%